2004
DOI: 10.1002/hlca.200490228
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Structure, Vibrational Spectra, and Hydrogen Bonding of the Ionic Liquid 1‐Ethyl‐3‐methyl‐1H‐imidazolium Tetrafluoroborate

Abstract: The IR and Raman spectra and conformations of the ionic liquid 1-ethyl-3-methyl-1H-imidazolium tetrafluoroborate, [EMIM] [BF 4 ] (6), were analyzed within the framework of scaled quantum mechanics (SQM). It was shown that SQM successfully reproduced the spectra of the ionic liquid. The computations revealed that normal modes of the EMIM ¥ BF À 4 ion pair closely resemble those of the isolated ions EMIM and BF À 4 , except for the antisymmetric BF stretching vibrations of the anion, and the out-of-plane and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
165
3
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(187 citation statements)
references
References 22 publications
15
165
3
4
Order By: Relevance
“…Combined, these data indicate the ion pairing persists in the CD 3 CN solvent, at least to some extent, and the main contact is between the anion and the ring proton at the 2-position as expected. [30,31] In addition, the IR spectra of salts 2-7 show characteristic absorptions of the imidazolium ring. It has been reported that ionic liquids tend to form cation-anion aggregates and these aggregates have been investigated by ESIMS.…”
Section: Resultsmentioning
confidence: 98%
“…Combined, these data indicate the ion pairing persists in the CD 3 CN solvent, at least to some extent, and the main contact is between the anion and the ring proton at the 2-position as expected. [30,31] In addition, the IR spectra of salts 2-7 show characteristic absorptions of the imidazolium ring. It has been reported that ionic liquids tend to form cation-anion aggregates and these aggregates have been investigated by ESIMS.…”
Section: Resultsmentioning
confidence: 98%
“…À anion in neat [C 2 mim][BF 4 ]; a finding that was later confirmed by IR and Raman spectroscopy [67]. The degree of hydrogen bonding between the ringbound hydrogen atoms and the anion seems to change significantly when going from e.g., a neat chloride to a hexafluorophosphate.…”
Section: N]mentioning
confidence: 85%
“…Similarly, studies were done on [C 2 mim][BF 4 ] and other 1-ethyl-3-methylimidazolium liquid salts [67,127,137]. In the Raman spectral range 200-500 cm À1 , Umebayashi et al [137] for liquids contain- [127].…”
Section: Assigned To Vibrations Associated With the Imidazolium Ring mentioning
confidence: 99%
“…71−81 Spectral bands in the region from 3200 to 3000 cm −1 are attributed to the coupled aromatic ring C−H stretching vibrations of the imidazolium hydrogen atoms, while those between 3000 and 2850 cm −1 can be assigned to the aliphatic C−H stretches of the CH 2 and CH 3 groups of the ethyl chain and of the CH 3 group bonded directly to the [C 2 MIM + ] ring. [71][72][73][74][75][76][77][78]81 4 ] thin films to water vapor in the sealed ATR cell at different levels of RH at 295 K. After each RH adjustment, spectra were collected until the band intensities stopped changing to ensure that equilibrium was attained. It typically took ∼20 min for the system to equilibrate.…”
Section: ■ Introductionmentioning
confidence: 99%